Effects of Combined Movement and Storytelling Intervention on Fundamental Motor Skills, Language Development and Physical Activity Level in Children Aged 3 to 6 Years: Study Protocol for a Randomized Controlled Trial - Rodrigo Vargas-Vitoria; César Faúndez-Casanova; Alberto Cruz-Flores; Jordan Hernandez-Martinez; Stefany Jarpa-Preisler; Natalia Villar-Cavieres; María Teresa González-Muzzio; Lorena Garrido-González; Jorge Flández-Valderrama; Pablo Valdés-Badilla (MDPI AG, 2023)
This study protocol aims to analyze and compare the effects of combined movement and storytelling intervention (CMSI) on fundamental motor skills (locomotor skills and object control), language development (language comprehension, language expression, vocabulary and language description), and physical activity levels (light intensity, moderate-to-vigorous intensity and sedentary time) in children aged 3 to 6 years. The sample will consist of 144 children from 12 class groups, randomly assigned to 3 experimental groups (n = 72 children) and 3 control groups (n = 72 children), belonging to 4 class groups of upper-middle-level classes (2 experimental and 2 control; 3 to 4 years), 4 transition level 1 classes (2 experimental and 2 control; 4 to 5 years) and 4 transition level 2 classes (2 experimental and 2 control; 5 to 6 years). The experimental groups will perform CMSI for 3 sessions per week (40 min per session) over 12 weeks (using one motor story per week), while the control groups will not receive any treatment. The main outcome will provide information about fundamental motor skills, language development, and physical activity levels. Our hypothesis indicates that CMSI has the potential to generate significant increases in selected assessments. If this intervention proves to be beneficial, it could contribute to preschool and school curricula.